Digital Books in Libraries: Moving Towards a Sustainable & Equitable System of Access to Information - Rosenfeld, Megan; Andreassi, Erin (My University, 2022)
Over the past ten years, tensions have grown between libraries and the publishing industry as digital books have become more popular and as digital book costs have risen. As library workers, the researchers of this paper are motivated by the core mission of libraries to provide access to information, which is threatened by current licensing models. The researchers assessed the current practices and power imbalances of digital book licensing through interviews with 40 stakeholders. This research suggests that legislation is one of many possible strategies to achieve a sustainable and equitable system of access to information for future generations.